PENINGKATAN KEMAMPUAN BERPIDATO SISWA KELAS VI SEKOLAH DASAR NEGERI ARCA KECAMATAN SUKAMAKMUR KABUPATEN BOGOR MELALUI TEKNIK STAND UP COMEDY - Sukron, Asep (Universitas Negeri Surabaya, 2019)
ABSTRACTThe purpose of this research was to improve the ability of public speaking’s student by using stand up comedy technique of grade sixth SDN Arca subdistrict Sukamakmur, Bogor. The subject consisted of 30 students, 12 males, 18 females. The problems in this research is the low ability of speaking’s student in therms linguistic factors or nonlingusitic factors. Besides that, the learning are not interesting, boring and the result of the learning have not reached minimum completenes criteria established by school. This study was classroom action research (CAR) it was conducted with two cycles, each cycle consisted of planning, conducting, observation, and reflection of Kemmis and Taggart Model. Related with the quality of student’s learning result by using stand up comedy technique, it showed that student’s abilities were improved. These abilities were regularity the delivery of ideas, sentence and word accuracy, fluency and naturalness, articulation and intonation, courage and trust, the precision of set up and punch line technique, the precision of one liner technique, and the precision of act out technique. The Results of research on learning cycle one, indicating that speech abilities of students through the techniques of stand up comedy has increased by 67% and the end of the second cycle of 90%. Based on data analysis, found an increased percentage of students in speech amounted to 23%. It can be concluded that learning through stand up comedy techniques to improve the ability of speech sixth grade students of SDN Arca Sukamakmur District of Bogor regency on the initial hypothesis can be accepted and proven. Key Words: Stand Up Comedy Technique, Speaking Ability of Student. ABSTRAKPenelitian ini bertujuan untuk meningkatkan kemampuan berpidato melalui teknik stand up comedy pada siswa kelas VI SDN Arca Kecamatan Sukamakmur Kabupaten Bogor dengan subjek 30 siswa, terdiri atas 12 siswa laki-laki dan 18 siswi perempuan. Permasalahan dalam penelitian ini adalah rendahnya kemampuan berbicara siswa dalam hal faktor-faktor kebahasaan maupun nonkebahasaan. Di samping itu, pembelajaran kurang menarik, membosankan, dan hasil pembelajaran belum mencapai Kriteria Ketuntasan Minimal (KKM) yang ditetapkan oleh Sekolah. Penelitian ini adalah Penelitian Tindakan Kelas (PTK) yang dilaksanakan dalam 2 siklus, setiap siklus terdiri atas perencanaan, pelaksanaan, observasi dan refleksi model Kemmis dan Taggart. Berkenaan dengan kualitas kemampuan berpidato anak dengan teknik stand up comedy menunjukkan bahwa kemampuan siswa dapat meningkat. Kemampuan tersebut adalah keruntutan penyampaian gagasan, ketepatan kalimat dan kata, kelancaran dan kewajaran, artikulasi dan intonasi, keberanian dan percaya, ketepatan set up dan punch line, ketepatan teknik one liner, dan ketepatan teknik act out. Hasil penelitian pada pembelajaran siklus I, menunjukkan bahwa kemampuan berpidato siswa melalui teknik stand up comedy mengalami peningkatan sebesar 67% dan akhir siklus II sebesar 90%. Berdasarkan analisis data tersebut, ditemukan persentase peningkatan siswa dalam berpidato sebesar 23%. Sehingga dapat disimpulkan bahwa pembelajaran melalui teknik stand up comedy untuk meningkatkan kemampuan berpidato siswa kelas VI SDN Arca Kecamatan Sukamakmur Kabupaten Bogor pada hipotesis awal dapat diterima dan terbukti. Kata kunci: Teknik Stand Up Comedy, Kemampuan Berpidato Siswa.